Utilization of sewage-sludge-derived hydrochars toward efficient cocombustion with different-rank coals : effects of subcritical water conversion and blending scenarios - Wang, Jing-Yuan (2015)
In the absence of prior drying, dewatered sewage sludge (DSS) was directly converted to hydrochars with superior fuel characteristics in subcritical water. Hydrochar derived at 320 °C and 12.0 MPa (SHC-320) was screened for systematic cocombustion with different-rank coals. The results suggest that SHC-320 reduced the activation energy of the blends and altered the main combustion profiles. Meanwhile, blending of SHC-320 induced greater heat loss for higher-rank coals, whereas a higher portion of SHC-320 further improved the ignition reactivity of high-rank coal blends. In the high-temperature region, the value of the pre-exponential factor increased with increasing coal/SHC-320 ratio, resulting in more intense synergistic effects in blends. At a low coal/SHC-320 ratio (30:70), intense antisynergistic effects occurred in cocombustion with low- or high-rank coals. As a result of distinct synergistic interactions, cocombustion with moderate-rank coal achieved the best combustion efficiency among the blends. These findings benefit efficient utilization of DSS as a hydrochar solid fuel in existing cofiring power plants.